Finite Sample Distributions Associated with Stochastic Difference Equations–Some Experimental Evidence - Basmann, R. L.; Richardson, D. H.; Rohr, R. J. (Econometrica, 1974)
R. L. Basmann, D. H. Richardson, R. J. Rohr, Finite Sample Distributions Associated with Stochastic Difference Equations–Some Experimental Evidence, Econometrica, Vol. 42, No. 5 (Sep., 1974), pp. 825-839